1966
DOI: 10.1007/bf02646791
|View full text |Cite
|
Sign up to set email alerts
|

Biodegradation studies on ap,tert.‐octylphenoxypolyethoxyethanol

Abstract: Recent results have suggested thatp,tert.‐octylphenoxynonaethoxyethanol (OPE10) has a high degree of degradability. These results have been confirmed and extended. The loss of response to cobalt thiocyanate under a wide variety of laboratory test conditions demonstrates that OPE10 will readily undergo bacterial attack. Significant loss of foaming and ethylene oxide in laboratory continuous and semicontinuous activated sludge units and septic tank‐percolation field units demonstrate that the degree of degradati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

1971
1971
1996
1996

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“…Similarly, Pitter and Fuka [41] found an initial rapid rate of biodegradation for Slovafoly, an NPEO with 3 to 35 ethoxylate units, within 7 DPT. Extensive biodegradation (Ͼ90%) also occurred within 14 DPT for shake-culture tests where NPEOs were placed in flasks with a bacterial-inoculated medium [42,43]. NPEO concentrations for this study likely stabilized after 14 DPT because the remaining surfactant partitioned to the sediment and thereby reduced its availability for biodegradation [18].…”
Section: Fate Of Rodeo and X-77 Spreadermentioning
confidence: 99%
“…Similarly, Pitter and Fuka [41] found an initial rapid rate of biodegradation for Slovafoly, an NPEO with 3 to 35 ethoxylate units, within 7 DPT. Extensive biodegradation (Ͼ90%) also occurred within 14 DPT for shake-culture tests where NPEOs were placed in flasks with a bacterial-inoculated medium [42,43]. NPEO concentrations for this study likely stabilized after 14 DPT because the remaining surfactant partitioned to the sediment and thereby reduced its availability for biodegradation [18].…”
Section: Fate Of Rodeo and X-77 Spreadermentioning
confidence: 99%
“…An example (Fig. The importance of adequate acclimation of bacterial inocula in studying the biodegradation of surfactants has been mentioned in the literature (9,14,15). Bacterial inocula previously had been acclimated to both of these substrates for 14 days.…”
Section: (Sdandc 23) Jaocs January 1981 / 61amentioning
confidence: 99%
“…At one time, surfactant biodegradability was demonstrated by primary transformation or loss of the parent compound and loss of surfactant properties such as foaming (2,3). However, such an approach ignores the possibility that ecologically significant bioresistant intermediates may be formed from the parent surfactant.…”
Section: Introductionmentioning
confidence: 99%
“…However, APEO compounds typically have highly branched alkyl substituents, which prevent the oxidation pathway effective for straight-chain aliphatic compounds (17). The primary aerobic biotransformation pathway observed for branched APEO is through shortening of the EO chain by hydrolysis or an oxidative-hydrolytic mechanism (2,16,18,19). Several investigators have found that APEO degrades to a relatively recalcitrant metabolite with two ethoxy units remaining on the intact aromatic ring with its alkyl substituent (3,16,20).…”
Section: Introductionmentioning
confidence: 99%